Pseudomonas aeruginosa as a priority group representative of bacteria with multiple antibiotic resistance - Vashchyk, Yevheniia; Morozenko, Dmytro; Seliukova, Nataliia; Zakhariev, Andriy; Dotsenko, Roman; Zemlianskyi, Andrii; Shapovalova, Olga; Dotsenko, Ekaterina (ScienceRise: Biological Science, 2021)
The aim: the aim of the research is an analytical review of the scientific literature on Рseudomonas aeruginosa as a priority group representative of bacteria with multiple antibiotics resistance. Materials and methods. The research was conducted by the method of scientific literature open source analysis: PubMed, Elsevier, electronic resources of the National Library named after V. I. Vernadsky and others. Results. The problem of antibiotic resistance is rightly called the “apocalypse of the XXI century”. P. aeruginosa bacteria are characterized by a very high natural ability to form resistant forms to antimicrobial drugs due to the formation of specific resistance genes, the ability to resist the entry of antibiotics into the cell or remove antibiotics from the cell, and form biofilms. A characteristic feature of the epidemic and epizootic processes of P. aeruginosa, as an opportunistic ubiquitous microorganism is host-pathogenic interaction - the interaction of the pathogen with the host organism. The peculiarity of this bacterium is opportunism and long-term persistence in the body of the host and in the environment. The global trend towards the spread of antibiotic-resistant gram-negative bacteria, including P. aeruginosa, underscores the need to develop comprehensive response strategies targeting all sectors of health. Conclusions. Bacteria P. aeruginosa is classified in 1th Critical Group of the WHO list of resistant to antibiotics "priority pathogens". Among the main reasons that contribute to the emergence of resistance are irrational antibiotic therapy in both humans and animals, and the use of antibiotics as growth stimulants in animal husbandry. While more R&D is vital, alone, it cannot solve the problem. To address resistance, there must also be better prevention of infections and appropriate use of existing antibiotics in humans and animals, as well as rational use of any new antibiotics that are developed in future. New methods of combating antibiotic resistance and antibacterial substances, alternatives to antibiotics (biofilm-destroying drugs, antimicrobial peptides (AMP), bacteriophages, nanopreparations, etc.) can make a positive contribution to overcoming the multiple drug resistance of gram-negatives